Molecular phylogeny inferred from mitochondrial DNA of the grouper Epinephelus spp. in Indonesia collected from local fish market - EDWIN JEFRI; NEVIATY P. ZAMANI; BEGINER SUBHAN; HAWIS H MADDUPPA (Society for Indonesian Biodiversity, 2015)
Jefri E, Zamani EP, Subhan B, Madduppa HH. 2015. Molecular phylogeny inferred from mitochondrial DNA of the grouper Epinephelus spp. in Indonesia collected from local fish market. Biodiversitas 16: 254-263. Groupers are widely distributed in thetropical and subtropical coastal waters, and are globally one of the most commercially important groups of marine fish, commandinghigh market price and are being heavily targeted in fisheries. Over fishing in Indonesia becomes a pivotal factor, which is seriouslythreatening the grouper biodiversity, as separate catch statistics are not reported for most species, and landings are often summarized as‘serranids’ or ‘groupers’. This lack of species-specific catch data is due to the difficulty of identifying many of the species. The focus ofthis study was the tracking of molecular phylogeny of Epinephelus spp. of the family Serranidae. DNA amplification usingmitochondrial cytochrome oxidase I resulted in 526-base pairs long sequences all samples. A total of seven species were characterizedthat are (Epinephelus areolatus, E. merra, E. fasciatus, E. longispinis, E. coioides, E. ongus and E. coeruleopunctatus). All of whichwere found to belong to 7 different clades in the constructed phylogenetic tree. E. ongus is genetically closest to E. coeruleopunctatuswith genetic distance 0.091 (9%), whereas the farthest genetic distance was successfully identified between E. ongus and E. merra withgenetic distance 0.178 (18%). Migration activity on spawning and movement of larvae that are affected by Indonesian Through flowsuspected as the cause of the closeness between species grouper Epinephelus spp. in the phylogeny tree from several Indonesian seas,although information about the location and time of Epinephelus spp. spawning activity sometimes difficult to obtain certainty. Fishidentification using molecular phylogenetic approach has been successfully applied in this study. It seems need further application onthis method to avoid misidentification and due to high variety of species landing at local fish market. Nevertheless, this study would bean important data in the genetic management for the sustainable conservation and trade of grouper (Epinephelus spp.) in Indonesia.